Facial wrinkles correction through autologous fat microinjection. - Heriberto Cháves Sánchez; Liliana Espinosa Chang (Medisur)
Background: autologous fat microinjection is a technique which allows the correction of different dispositions that appear in the face in a very fast, effective and simple way compared to other procedures implying more pain, incisions, and elevated doses of anesthesia. Objective: to show the effectiveness of the autologous fat microinjection in the correction of facial wrinkles. Methods: a series study was carried out from May 2005 to May 2006 at the University Hospital “Dr. Gustavo Aldereguía Lima” in Cienfuegos city, Cuba. 60 patients of both sexes constituted this series study. They had facial wrinkles and this procedure was performed on them. Age, sex, patient’s race, localization and the type of wrinkle as well as the satisfaction level of the patient with the surgical procedure were analyzed. Results: Female sex was predominant, as well as white race and the ages from 45-50. A good aesthetic result was obtained. The satisfaction level of the patients was more elevated in short and medium terms. Conclusions: the level of satisfaction reached in the studied series reassure the advantages of the autologous fat microinjection technique so that, it is recommended for the elimination of facial wrinkles.